Theodore Harris, Charter and Ordinances of the City of San Antonio. Comprising All Ordinances of a General Character in Force August 7th, at 220 (1899), Ordinances of the City of San Antonio, Ordinances, ch. 22, § 4 - (:unkn) unknown (General Publisher, 1899)
Prohibited drawing in a threatening manner a pistol, gun, knife, sword cane, club or any other instrument or weapon that may cause death.
--
Keywords: BRANDISHING